(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article we see that verb category is related to thepersons action, behavior, look objective conditions that act in communicative act. In the… «Khargyn» roman by D. Isabekov with the using verb categories we see the connection between peoples spiritual wealth and mentality. The roman considers language and person together there given attention to person as a cognitor of grammatical categories and the main subject of using the language.The article analyse this particularity of verb category. There were given several verb from … «Khargyn» roman and was Pinned the ways of their derivating. Also the authors verb category using is pin by the rate number